2016
DOI: 10.1117/1.jbo.21.9.098001
|View full text |Cite
|
Sign up to set email alerts
|

Lesion strength control by automatic temperature guided retinal photocoagulation

Abstract: Laser photocoagulation is an established treatment for a variety of retinal diseases. However, when using the same irradiation parameter, the size and strength of the lesions are unpredictable due to unknown inter- and intraindividual optical properties of the fundus layers. The aim of this work is to investigate a feedback system to generate desired lesions of preselectable strengths by automatically controlling the irradiation time. Optoacoustics were used for retinal temperature monitoring. A 532-nm continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Our research group has previously reported on temperature-guided retinal photocoagulation with optoacoustic feedback. Koinzer et al 15 , 20 established a fixed-power variable-time approach, where a constant irradiation power was held until the desired aim temperature was reached. This was a first step toward more reproducible and uniform lesion strengths based on the Arrhenius damage integral accounting for the temperature and time of elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has previously reported on temperature-guided retinal photocoagulation with optoacoustic feedback. Koinzer et al 15 , 20 established a fixed-power variable-time approach, where a constant irradiation power was held until the desired aim temperature was reached. This was a first step toward more reproducible and uniform lesion strengths based on the Arrhenius damage integral accounting for the temperature and time of elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure transients are recorded by an ultrasonic transducer (Medical Laser Center Lübeck, Lübeck, Germany) embedded in the contact lens and digitized by a data acquisition board. 17 , 20 A control-unit processes the data in real time to acquire the temperature rise.…”
Section: Methodsmentioning
confidence: 99%
“…In order to meet the need for proper energy dosing, Brinkmann et al [13] have developed an approach for online temperature measurement during retinal laser treatment using the photo-acoustic effect. It has already proven its feasibility during animal experiments on rabbits [9,14] and even in clinical studies [13]. Briefly, if a sufficiently short light pulse from the probe laser is absorbed by the RPE, the impulsive expansion gives rise to a pressure transient, which can be detected at the exterior corneal surface of the eye by means of an ultrasonic transducer.…”
Section: Introductionmentioning
confidence: 99%
“…30 The creation of lesions of different strengths was also demonstrated on rabbits in vivo. 31,32 In this work, we present an alternative approach for a temperature-based feedback control, which adjusts the therapy laser power during the irradiation, in order to achieve a preset temperature rise within a fixed time frame.…”
Section: Introductionmentioning
confidence: 99%